Sea cucumber sulfated polysaccharides extract potentiates the anticancer effect of 5- fluorouracil on hepatocellular carcinoma cells - Samah E. Ismail; Neveen A. Hussein; Mona M. Rashad; Amany M. El-Sikaily; Abd El-Latif A. Hassanin; Esmail M. El-Fakharany (Scientific Reports)
Abstract Sea cucumber represents a potential marine source of high value compounds with medicinal properties especially its anti-cancer activity. Sea cucumbers contain numerous biomolecules, including sulfated polysaccharides (Ps) which have enormous therapeutic and nutraceutical potential. This study aimed to investigate anticancer effect of Ps extracted from sea cucumbers on hepatocellular carcinoma. This study was in vitro study conducted on HepG-2 cells and normal wish cells that were divided into four groups: Group I including untreated cells, Group II including cells treated with different concentrations of 5-FU, Group III including cells treated with various concentrations of Ps extract. Group IV including cells treated with different concentrations of combined 5-FU and Ps extract. The extracted Ps were characterized using FT-IR, HPLC, and GC–MS. The anticancer effect of Ps extract was determined using cytotoxicity MTT assay, DNA fragmentation assay, wound healing assay, colony formation and soft agar assay. Also, the effect of Ps extract on VEGF, survivin, BAX and BID gene expression was determined by qRT-PCR and its effect on Bcl2 and BAK protein level was determined by western blotting technique. The results indicated that sea cucumber Ps extract either alone or in combination with 5-FU reduced HepG-2 and wish cell viability with higher selectivity index. Also, it inhibited both adherent and non-adherent colony forming ability and cell migration of HepG-2 cells. Moreover, it was significantly downregulated VEGF, survivin and Bcl2 while, it was significantly upregulated BAX, BAK and BID. In conclusion, sea cucumber Ps extract may be an effective chemotherapeutic agent against HCC.